LOCALIZATION ALGORITHM FOR MULTILATERATION SYSTEMS - A. A. Monakov (Известия высших учебных заведений России: Радиоэлектроника, 2018)
At present, multilateration systems are becoming increasingly  important in air traffic control.  This is due  to their significant advantages in compare with secondary surveillance  radar complexes. This article solves the problem of synthesizing an algorithm for object location estimation for multilateration system operating in passive mode. The synthesized algorithm is a combination of a procedure, the result  of which is a rough  estimate of the observed object  coordinates, and  an iterative  algorithm specifying  the resulting solution.  The rough estimate is the result of solving a linear system of equations. The iterative  refinement procedure is based  on the linearization of the observational equations and does not require a large number of iterations. The paper provides  a comparative statistical  analysis  of the  proposed algorithm and  the  known  Bancroft  algorithm. For an objective analysis of two algorithms, the paper derives the Cramer-Rao boundary for the correlation matrix of estimates of the observed object coordinates, which makes it possible  to determine the potential accuracy of the solution  of the problem. It is shown  that both algorithms allow obtaining estimates, the accuracy of which is close to the potentially achievable accuracy of the object location estimate. In contrast to the Bancroft  algorithm, the rough estimate of the object location is unambiguous. This virtue reduces  the total amount of computations during the algorithm implementation and reduces  the probability of anomalous errors.